Cuantificación de hongos y micotoxinas en alimento balanceado proveniente de granjas avícolas en Ucayali, Perú - Guevara A., Iván (2025)
The aim of this study was to quantify fungi and mycotoxins in feeds stored in poultry farms. Feed samples were collected from 40 farms located in four districts of the province of Coronel Portillo, Ucayali, Peru. They were analysed through plate count for fungi in feed to determine quality (satisfactory, acceptable or unacceptable) and competitive ELISA test for mycotoxins (aflatoxin B1, ochratoxins, T2 toxin, fumonisin B1 and zearalenone). In the fungal count, 25% (10/40) of farms had unacceptable samples, with a slightly higher frequency from the laying stage (2/4, 50%) and the Campo Verde district (4/10, 40%). The highest averages in the counts were from the laying samples and from the Manantay district, respectively (1.68 x 105 and 1.11 x 105 CFU/g, respectively), but with no association between feed quality by type or origin (p>0.05). Moreover, 60% of the samples had aflatoxin B1 above the maximum permissible limits (MPL), with a slightly higher frequency in the laying samples (4/4, 100%), but with no difference in the feed by district (p>0.05). The starter feed and Callería district had slightly higher averages of aflatoxins, but with no significant differences between types or origin (p>0.05). Minimal amounts of the other mycotoxins were found. It is concluded that 25% of the samples were in unacceptable conditions and 60% were samples contaminated with aflatoxin B1 (>MPL).